International Migration and Migration Policy Reforms - A. A. Tkachenko (Мир новой экономики, 2024)
The article examines the problems of regulating illegal migration by developed countries and the European Union, the achievements that cause not always correct criticism, and the possibilities of using the experience of a number of countries and new approaches in this regulation are shown. Particular attention is paid to international organizations dealing with the problems of international migration. It was concluded that there is no clear division of their functions by type of migration, which prevents the formation of long-term policies. Proposals were formulated to strengthen the role of the International Labour Organization (ILO) in rule-making and norm-setting on labor migration, which plays an increasingly important role in sustainable development. It was concluded that it is necessary to change the status of the migration conventions, otherwise effective regulation of labor migration is impossible. The countries of the Persian Gulf that attract external labor immigrants despite the rapid growth of the local population are highlighted. The difference in countries’ policies towards labor migration in the 21st century compared to the 20th century is shown. The concept of “fiduciary duty” of federal governments in relation to external migration was introduced.